COMBINED VERSUS SINGLE-MODALITY LIFESTYLE INTERVENTIONS ON INSULIN RESISTANCE AND HORMONAL PARAMETERS IN WOMEN WITH POLYCYSTIC OVARY SYNDROME: A STRUCTURED NARRATIVE REVIEW - Badowska, Natalia; Matuszek, Izabela; Wiśniewski, Bartosz; Pachnowska, Dominika; Pluta, Natalia; Nowak, Katarzyna Aleksandra; Rutkowska-Nowosielska, Alicja; Czekanow, Oliwia Nikola; Kania-Bonicka, Zofia; Demkow, Jerzy (International Journal of Innovative Technologies in Social Science, 2026)
Background: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age, with an estimated global prevalence of 8-13% depending on the population studied and diagnostic criteria applied. Its pathophysiology involves insulin resistance (IR) and hyperandrogenism, which mutually reinforce each other: elevated insulin drives ovarian androgen overproduction and suppresses sex hormone-binding globulin (SHBG), while excess androgens themselves worsen IR. Both IR and hyperandrogenism are modifiable through lifestyle interventions - specifically dietary modification and physical activity - making them the primary targets of non-pharmacological management in PCOS. Lifestyle interventions are recommended as first-line therapy, but the comparative effectiveness of combined versus single-modality approaches on IR and hormonal parameters remains unclear.Aim: To synthesise and compare the effects of combined lifestyle interventions (diet plus exercise) versus single-modality approaches (diet alone or exercise alone) on markers of insulin resistance and key hormonal parameters in women with PCOS.Material and methods: A comprehensive literature search was conducted across PubMed/MEDLINE, Embase, and Cochrane Library databases. Search terms included polycystic ovary syndrome, PCOS, insulin resistance, HOMA-IR, lifestyle intervention, combined intervention, diet, exercise, testosterone, and SHBG. Studies evaluating lifestyle interventions in women with PCOS and reporting insulin resistance and/or hormonal outcomes were included, with no restriction on study design.Results: Both single-modality and combined interventions improved insulin sensitivity and hormonal profiles. Available evidence suggests that combined diet-and-exercise programmes may produce broader improvements in metabolic (HOMA-IR, fasting insulin) and hormonal (free testosterone, SHBG) markers than either approach applied alone; however, direct comparative evidence remains limited and heterogeneous. Vigorous aerobic exercise and resistance training have been associated with the strongest independent effects on IR in the reviewed evidence, while low-glycaemic-index and Mediterranean diets improved hormonal balance through complementary mechanisms - principally reduction of postprandial hyperinsulinaemia and attenuation of chronic low-grade inflammation respectively.Conclusions: The available evidence suggests that combined lifestyle interventions may produce greater improvements in insulin resistance and hormonal parameters in women with PCOS than single-modality approaches, though the current evidence base is limited by the quality and number of available trials. Consistent with this, international guidelines recommend multimodal programmes integrating structured exercise with evidence-based dietary strategies as first-line PCOS care. Further large-scale randomised controlled trials directly comparing combined versus single-modality protocols are needed.